Long-term neutralization capacity of vaccine and breakthrough infection induced SARS-CoV-2 specific antibodies against omicron subvariants BA.2, XBB.1.5, and JN.1 - Reinholm, Arttu; Khan, Hira; Laakso, Terhi; Maljanen, Sari; Jalkanen, Pinja; Gunell, Marianne; Kallonen, Teemu; Österlund, Pamela; Ritvos, Olli; Nousiainen, Arttu; Häkkinen, Hanni K.; Pakkanen, Sari H.; et al. (Elsevier, 2026)
The long-term effectiveness of COVID-19 vaccines remains a critical area of study, especially with the emergence of new SARS-CoV-2 subvariants. In this study, we investigated the long-term neutralization capacity of SARS-CoV-2 -specific antibodies induced by the third, fourth and fifth vaccine doses, and by SARS-CoV-2 breakthrough infections. Spike (S)-specific antibodies decline relatively rapidly after each vaccine dose, with an estimated half-life of 3–4 months. However, after the third vaccine dose, S-specific serum antibody levels remained comparable at 12 and 24 months post-vaccination. Antibody levels induced by the fourth and fifth vaccine doses were higher, and the decay was slower than after the third vaccine dose. Additionally, nucleocapsid (N)-specific antibody levels increased significantly following multiple breakthrough infections. The neutralization capacity of the antibodies against Omicron XBB.1.5 and JN.1 subvariants were significantly increased by the fifth, XBB.1.5 subvariant specific, mRNA vaccine dose. Our findings strongly indicate that updated booster vaccines based on the latest s of concern are necessary to sustain high neutralizing antibody levels against emerging variants. No exhaustion of vaccine-induced antibody response was observed after repeated COVID-19 vaccinations.